European Companies' Readiness and Challenges in Data Economy - Heikkilä, Marikka; Heikkilä, Jukka; Ahmad, Farhan (Slovenia, 2025)
This study investigates the readiness and challenges European companies face in embracing a data-driven economy. By conducting a comprehensive survey of 1,200 European companies spanning various industries and sizes, we reveal a mixed outlook on the data economy's potential to offer a competitive advantage. We find that 20% have already leveraged data to gain competitive advantage, a majority see potential benefits, while 19% perceive no advantage. Importantly, our findings highlight the need for substantial business model transformations to capitalize on data-driven opportunities. The paper also identifies the obstacles faced by companies in adopting a data-driven approach, including legal complexity, lack of data, competence in data-driven business models and technological competence. Challenges are most pronounced among micro-sized businesses and sectors like arts, entertainment, leisure, and international NGOs. Overall, the research suggests that if the company has the skills, a data economy has the potential to drive innovation and growth. By identifying the disparities in readiness and perception across different sectors and company sizes, this study contributes to a more informed discourse on fostering a conducive environment for all companies to thrive in the data-driven economy.
37th Bled eConference – Resilience Through Digital Innovation: Enabling the Twin Transition: June 9 – 12, 2024, Bled, Slovenia, Conference Proceedings